Doxercalciferol Alleviates Bone Deteriorations and Cartilage Degeneration in Aging Mice - Li, Jian; Li, Nan; Yan, Shuangtong; Liu, Minyan; Sun, Banruo; Lu, Yanhui; Shao, Yinghong (Experimental and Clinical Endocrinology & Diabetes, 2018)
Background Age-related bone deteriorations are the common endocrine disorders in the elderly population, leading to an increased risk of fractures. Therefore, effective treatment strategies provide a way to prevent bone loss and improve the quality of life in the elderly population. The present study aimed to investigate the anti-osteoporotic effects of doxercalciferol (DOX) in aging mice.Methods Bone metabolism-related markers were measured by ELISA assay. The expression of bone formation and resorption-related genes was performed by RT-qPCR analysis. Hematoxylin and eosin (H&E) and Safranin O staining were performed to analyze the trabecular bone and cartilage degeneration.Results Aging resulted in urine ca2+ excretion, a decrease in bone ca2+ content and reduction of biomechanical strength in mice. We also found that the level of PTH was increased in aging mice, while DOX administration markedly down-regulated serum PTH in aging mice. H&E and Safranin O staining showed that DOX protected against aging-induced bone loss and cartilage regeneration in the tibia from aging mice. Furthermore, DOX treatment resulted in an increase in Runx2, osterix and Col1a1 mRNA expression and a decrease in Ctsk, MMP-9 and CAII mRNA expression in the tibia from aging mice.Conclusion These findings indicated that DOX had a beneficial effect on age-related bone deteriorations in aging mice by promoting osteoblast activity and cartilage regeneration and inhibiting osteoclast-specific genes expression.
Keywords: doxercalciferol; osteoporosis; aging; skeleton; PTH